2009
DOI: 10.1007/s00477-008-0301-z
|View full text |Cite
|
Sign up to set email alerts
|

The ensemble particle filter (EnPF) in rainfall-runoff models

Abstract: Rainfall-runoff models play a very important role in flood forecasting. However, these models contain large uncertainties caused by errors in both the model itself and the input data. Data assimilation techniques are being used to reduce these uncertainties. The ensemble Kalman filter (EnKF) and the particle filter (PF) both have their own strengths. Research was carried out to a possible combination between both types of filters that will lead to a new type of filters that joins the strengths of both. The so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Since the PF needs to resolve higher-order distribution properties that are ignored by the EnKF, more particles may be required in the implementation of the PFs for reliable comparisons with the EnKF. In a recent study, 500 particles were chosen for assimilation to achieve reliable comparisons between the PF and the EnKF for rainfall runoff [50]. Zhou et al [54] found that particle sizes greater than 800 resulted in nearly the same RMSEs between the PF and the EnKF for root zone soil moisture.…”
Section: Comparison Of Pf and Enkfmentioning
confidence: 98%
“…Since the PF needs to resolve higher-order distribution properties that are ignored by the EnKF, more particles may be required in the implementation of the PFs for reliable comparisons with the EnKF. In a recent study, 500 particles were chosen for assimilation to achieve reliable comparisons between the PF and the EnKF for rainfall runoff [50]. Zhou et al [54] found that particle sizes greater than 800 resulted in nearly the same RMSEs between the PF and the EnKF for root zone soil moisture.…”
Section: Comparison Of Pf and Enkfmentioning
confidence: 98%
“…Weerts and El Serafy (2006) compared the capabilities of the EnKF with the particle filter at improving flood forecast predictions using the quasi-distributed HBV-96 model and reported that the EnKF outperformed the particle filter at low flow conditions and when the ensemble size was small. Using the HyMOD, Van Delft et al (2009) proposed an approach for combining ensemble Kalman filter and particle filter algorithms. In their analysis they relied on small ensemble sizes (\150) which was the basis in their conclusion about the performance of each procedure neglecting the fact that the particle filter can provide better result when more particles are used (Moradkhani et al 2005b;Zhou et al 2006).…”
Section: Sequential Bayesian Estimation Using Monte Carlo Simulationmentioning
confidence: 99%
“…This calls for online estimation (also known as filtering), i.e. computations of estimates for the unknown or unmeasurable states of a time-varying system simultaneously as measurements for the system are obtained [4][5][6][7]. However, some state variables in wastewater treatment processes cannot be directly measured online (e.g.…”
Section: Introductionmentioning
confidence: 98%